Matrix-Immobilized BMP-2 on Microcontact Printed Fibronectin as an in vitro Tool to Study BMP-Mediated Signaling and Cell Migration - Hauff, Kristin; Zambarda, Chiara; Dietrich, Miriam; Halbig, Maria; Grab, Anna Luise; Medda, Rebecca; Cavalcanti-Adam, Elisabetta Ada (Frontiers in Bioengineering and Biotechnology, 2015)
During development, bone morphogenetic proteins (BMPs) exert important functions in several tissues by regulating signaling for cell differentiation and migration. In vivo the extracellular matrix (ECM) not only provides a support for adherent cells, but also presents a reservoir of growth factors (GFs). Several constituents of the ECM provide adhesive cues, which serve as binding sites for cell transmembrane receptors, such as integrins, which convey adhesion-mediated signaling to the intracellular compartment. Integrins do not function alone but rather crosstalk and cooperate with other receptors, such as GF receptors, in regulating cell responses to extracellular signals. To this, we present here the immobilization of BMP-2 onto cellular fibronectin (cFN), a key protein of the ECM, to investigate their impact on GF-mediated signaling and migration. Following biotinylation, BMP-2 was linked to biotinylated cFN using NeutrAvidin (NA) as cross-linker. Characterization with QCM-D and ELISA confirmed the efficient immobilization of BMP-2 on cFN over a period of 24 h. To validate the bioactivity of matrix-immobilized BMP-2 (iBMP-2) we investigated short- and long-term responses of C2C12 myoblasts in comparison to soluble BMP-2 (sBMP-2) or in absence of GFs. Similarly to sBMP-2, iBMP-2 triggered Smad 1/5 phosphorylation and translocation into the nucleus corresponding to the activation of BMP-mediated Smad-dependent pathway. Additionally, successful suppression of myotube formation was observed after six days. We next implemented this approach to fabricate cFN micro patterned stripes by soft lithography. These stripes only allowed cell-surface interaction on the pattern due to passivation of the surface in between, thus serving as platform for studies on directed cell migration. During a 10 h-period, cells showed an increased migratory activity upon BMP-2 exposure. Thus, this versatile tool retains the GF's bioactivity and allows the presentation of ECM adhesive cues.